Periprocedural acute haemodynamic decompensation during substrate-based ablation of scar-related ventricular tachycardia: a rare and unpredictable event - Stojadinović, Predrag; Wichterle, Dan; Peichl, Petr; Čihák, Robert; Aldhoon, Bashar; Borišincová, Eva; Štiavnický, Petr; Hašková, Jana; Ševčík, Adam; Kautzner, Josef (Europace, 2024)
AIMS: Patients with structural heart disease (SHD) undergoing catheter ablation (CA) for ventricular tachycardia (VT) are at considerable risk of periprocedural complications, including acute haemodynamic decompensation (AHD). The PAINESD score was proposed to predict the risk of AHD. The goal of this study was to validate the PAINESD score using the retrospective analysis of data from a large-volume heart centre. METHODS AND RESULTS: Patients who had their first radiofrequency CA for SHD-related VT between August 2006 and December 2020 were included in the study. Procedures were mainly performed under conscious sedation. Substrate mapping/ablation was performed primarily during spontaneous rhythm or right ventricular pacing. A purposely established institutional registry for complications of invasive procedures was used to collect all periprocedural complications that were subsequently adjudicated using the source medical records. Acute haemodynamic decompensation triggered by CA procedure was defined as intraprocedural or early post-procedural (<12 h) development of acute pulmonary oedema or refractory hypotension requiring urgent intervention. The study cohort consisted of 1124 patients (age, 63 ± 13 years; males, 87%; ischaemic cardiomyopathy, 67%; electrical storm, 25%; New York Heart Association Class, 2.0 ± 1.0; left ventricular ejection fraction, 34 ± 12%; diabetes mellitus, 31%; chronic obstructive pulmonary disease, 12%). Their PAINESD score was 11.4 ± 6.6 (median, 12; interquartile range, 6-17). Acute haemodynamic decompensation complicated the CA procedure in 13/1124 = 1.2% patients and was not predicted by PAINESD score with AHD rates of 0.3, 1.8, and 1.1% in subgroups by previously published PAINESD terciles (<9, 9-14, and >14). However, the PAINESD score strongly predicted mortality during the follow-up. CONCLUSION: Primarily substrate-based CA of SHD-related VT performed under conscious sedation is associated with a substantially lower rate of AHD than previously reported. The PAINESD score did not predict these events. The application of the PAINESD score to the selection of patients for pre-emptive mechanical circulatory support should be reconsidered.
Keywords: Female; Tachycardia, Ventricular; ženské pohlaví; plicní edém; jizva; Catheter Ablation; Hemodynamics; hemodynamika; lidé; katetrizační ablace; pooperační komplikace; Pulmonary Edema; Cicatrix; Risk Factors; retrospektivní studie; Male; Postoperative Complications; Hypotension; Aged; komorová tachykardie; rizikové faktory; hypotenze; lidé středního věku; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; Humans